Septic shock - V. O. Bitsadze; T. A. Sukontseva; S. V. Akinshina; Ya. Yu. Sulina; J. Kh. Khizroeva; M. V. Tretyakova; Kh. G. Sultangadzhieva; J. Yu. Ungiadze; N. V. Samburova; K. N. Grigoreva; V. I. Tsibizova; A. S. Shkoda; et al. (IRBIS LLC, 2020)
The problem of sepsis and septic shock has recently become more and more actual. In obstetrics and gynaecology, the number of cases of sepsis has more than doubled over the past 10 years. The review examines the clinical forms of septic conditions, risk factors, pathogenesis of sepsis and septic shock, the main pathogens of septic conditions. Special attention is paid to neonatal sepsis. The relationship between septic shock and viral infections is considered in the context of the novel coronavirus infection caused by SARS-CoV-2 (COVID-19) pandemic. Hemostasis abnormalities have been demonstrated in patients with septic shock, including disseminated intravascular coagulation (DIC). The importance of determining the level of ADAMTS-13 to refine the forecast is discussed.